Constraints on the origin of cosmic rays from large scale anisotropy searches in data of the Pierre Auger Observatory - De Almeida, Rogerio M.; Aab, A.; Sciutto, Sergio Juan; Tueros, Matias Jorge; Allekotte, Ingomar; Almela, Daniel Alejandro; Asorey, Hernán Gonzalo; Avila, G.; Bertou, Xavier Pierre Louis; Contreras, F.; De La Vega, B. R. G.; Dova, Maria Teresa; et al. (International Union of Pure and Applied Physics, 2013)
Fil: De Almeida, Rogerio M.. Universidade Federal Fluminense; Brasil